2017
DOI: 10.1038/ismej.2017.156
|View full text |Cite
|
Sign up to set email alerts
|

Microdiversification in genome-streamlined ubiquitous freshwater Actinobacteria

Abstract: Actinobacteria of the acI lineage are the most abundant microbes in freshwater systems, but there are so far no pure living cultures of these organisms, possibly because of metabolic dependencies on other microbes. This, in turn, has hampered an in-depth assessment of the genomic basis for their success in the environment. Here we present genomes from 16 axenic cultures of acI Actinobacteria. The isolates were not only of minute cell size, but also among the most streamlined free-living microbes, with extremel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
248
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(255 citation statements)
references
References 78 publications
6
248
1
Order By: Relevance
“…SAR11 is highly abundant in the oxygenated surface ocean and also in mOMZs (Wright et al ., ; Bertagnolli and Stewart, ). Similarities based on small genome and cell sizes between acI and SAR11 have been noted previously (Neuenschwander et al ., ). Here we find indications that acI lineages in meromictic Powell Lake, like SAR11 lineages from mOMZs (Tsementzi et al ., ), stand out from their strictly aerobic relatives by facultative anaerobic adaptations, notably the possession of genes for respiratory nitrate reduction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…SAR11 is highly abundant in the oxygenated surface ocean and also in mOMZs (Wright et al ., ; Bertagnolli and Stewart, ). Similarities based on small genome and cell sizes between acI and SAR11 have been noted previously (Neuenschwander et al ., ). Here we find indications that acI lineages in meromictic Powell Lake, like SAR11 lineages from mOMZs (Tsementzi et al ., ), stand out from their strictly aerobic relatives by facultative anaerobic adaptations, notably the possession of genes for respiratory nitrate reduction.…”
Section: Discussionmentioning
confidence: 97%
“…In Powell Lake, an OTU affiliated with acI dominated the oxycline and nitrogenous zones and remained prevalent even in the manganous zone (Table 1). Its closest neighbour (99% sequence identity, blastN) was Candidatus 'Planktophila vernalis' isolate MMS-IIA-15 (NZ_CP016776.1; Neuenschwander et al, 2018). The high relative abundance of acI within and below the oxycline may be due to undocumented facultative anaerobic adaptations in Powell Lake strains (Ghylin et al, 2014).…”
Section: Facultative Anaerobic Adaptations In Widespread Actinobactermentioning
confidence: 99%
“…Ice-covered conditions may favour microbes that have low resource requirements (i.e., oligotrophs) and small genome size is a common adaptation to oligotrophic conditions (Carini et al, 2013;Neuenschwander et al, 2017). Previous analysis of Verrucomicrobia MAGs have shown a wide range in genome sizes (Cabello-Yeves et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas nearly identical viral genomes have been reported from distant locations in marine environments, such as the Mediterranean Sea and Pacific Ocean , these results in freshwater systems are intriguing, as lakes and reservoirs are physically isolated from one another. By contrast, the genomes of their host (i.e., bacterioplankton) inhabiting different freshwater systems are generally distinct (Hahn et al, 2016;Kang et al, 2017;Garcia et al, 2018;Neuenschwander et al, 2018), although highly similar genomes (ANI >95%) have occasionally been reported from lakes on different continents (Mehrshad et al, 2018). The high phylogeographic connectivity of viruses was presumably because viruses can easily colonize a new habitat due to the lack of immunity by local hosts, whereas colonization by bacteria is often constrained by the priority effect, that is, occupation of the niche by prior inhabitants limits settlement of newly migrated genotypes (Incagnone et al, 2015).…”
Section: Viral Genomic Diversification Among Habitatsmentioning
confidence: 99%